A group approach to growing as a principal investigator - Greco, Valentina; Politi, Katerina; Eisenbarth, Stephanie; Colón-Ramos, Daniel; Giraldez, Antonio J; Bewersdorf, Joerg; Berg, David N (Current biology, 2022)
Greco et al. describe their experience learning to be more effective and humane PIs. The key to their growth was regular and consistent work with a diverse group of their peers aided by the guidance of an organizational psychologist.